LFO-coated all-solid-state lithium battery composite positive electrode material, preparation method and lithium-negative-electrode-free all-solid-state battery

By loading Li5FeO4 on the positive electrode material of all solid lithium batteries, the side reaction between the positive electrode material and the electrolyte and the increase in interface resistance are solved, the protection of the electrode active material and the compensation of active lithium are achieved, and the cycle stability of the battery is improved and energy density.

CN119480947APending Publication Date: 2025-02-18NANJING UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411415809.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In all-solid lithium batteries, there are side reactions between the positive electrode material and the electrolyte and the interface resistance increase, resulting in the structural degradation of the electrode active material and the decomposition of the electrolyte. Especially in all-solid lithium-free negative electrode batteries, the active lithium is rapidly depleted, resulting in the battery. Capacity decreases.

Method used

Li5FeO4 is loaded on the positive electrode material, and serves as a protective layer to suppress the structural degradation of the electrode active material and the decomposition of the electrolyte. At the same time, it is used as a prelithiating agent for the lithium-free negative electrode all-solid state battery to compensate for the depletion of active Li.

Benefits of technology

It effectively reduces the side reaction between the positive electrode and the solid electrolyte, inhibits the structural degradation of the electrode active material and the decomposition of the electrolyte, extends the cycle stability of the battery and improves the energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480947A_ABST
    Figure CN119480947A_ABST
Patent Text Reader

Abstract

The invention provides a nickel-rich layered oxide coated with Li5FeO4 (LFO) of an all-solid-state battery (ASSB) as a positive electrode of the all-solid-state battery, and a pre-lithiation agent LFO is used as an interface protection layer, so that on one hand, the lithium supplement effect is achieved in the battery, on the other hand, the reaction between a high-oxidability nickel-rich positive electrode and a sulfide solid electrolyte is prevented, the structure degradation of the nickel-rich positive electrode and the decomposition of SSE are reduced, and the service life of the battery is prolonged. Therefore, the excellent cycle life is obtained. Benefited from a coating LFO in a lithium-free negative electrode ASSB positive electrode, the reversible capacity and the capacity retention rate after charge and discharge cycles are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an LNO-coated all-solid-state lithium battery composite positive electrode material, a preparation method and a lithium-free negative electrode all-solid-state battery, belonging to the technical field of all-solid-state batteries. Background Art

[0002] Replacing liquid electrolytes with solid electrolytes (SSEs) in all-solid-state batteries (ASSBs) can reduce the risks associated with leakage and achieve higher energy density by using lithium metal anodes. In addition, lithium-free anodes and anode-free all-solid-state battery structures can be further designed to maximize gravimetric and volumetric energy densities. However, these advanced batteries suffer from obvious structural degradation of cathode materials, severe decomposition of SSEs at cathode interfaces, and rapid depletion of active Li at the cathode due to parasitic side reactions, which need to be urgently addressed.

[0003] The structural degradation of active materials and the decomposition of SSE on the cathode side are closely related. Chemical reactions at the interface between the cathode and SSE are usually spontaneous, leading to degradation and decomposition. In addition, the degradation and decomposition processes will be accelerated during repeated delithiation and lithiation. Degradation leads to slow diffusion kinetics, and decomposition leads to the formation of interfacial oxidation or reduction products with poor ionic conductivity, increased interfacial resistance, and reduced capacity. To address these obstacles, a common strategy is to insert a coating between the cathode material and SSE as a buffer layer to avoid adverse chemical / electrochemical reactions. Typically, the coating is limited to Li-Ion-compatible materials and SSEs. + Conductor materials, such as the typical LiNbO3. On the other hand, in lithium-free anode ASSBs, a large amount of active lithium is consumed due to severe side reactions on the negative electrode side, resulting in a decrease in battery capacity. Summary of the invention

[0004] In response to the problems of side reactions between the positive electrode material and the electrolyte and increased interface resistance in lithium-free negative electrode all-solid-state batteries, the present invention proposes a new manufacturing strategy for the positive electrode of all-solid-state batteries. By loading Li5FeO4 on the positive electrode, it serves as a protective layer between the positive electrode material and the electrolyte, inhibiting the structural degradation of the electrode active material and the decomposition of the electrolyte, and also simultaneously realizes the dual role of serving as a pre-lithiation agent for lithium-free negative electrode all-solid-state batteries.

[0005] The technical solution is:

[0006] A positive electrode material for a lithium-free negative electrode all-solid-state battery comprises: an electrode active material, a solid electrolyte, a conductive agent and Li5FeO4.

[0007] The electrode active material is selected from lithium-rich manganese-based positive electrode materials or high-nickel ternary positive electrode materials.

[0008] The solid electrolyte is selected from a polymer solid electrolyte, an oxide solid electrolyte, and a sulfide solid electrolyte.

[0009] The conductive agent is selected from one of carbon black, carbon fiber, carbon nanotube, conductive polymer and conductive metal.

[0010] The weight ratio of the electrode active material, the solid electrolyte, the conductive agent and Li5FeO4 is: 50-80:1-10:20-40:0.5-5.

[0011] The method for preparing the positive electrode material of the above-mentioned lithium-free negative electrode all-solid-state battery comprises the following steps:

[0012] Step 1, ball milling Li5FeO4;

[0013] Step 2: The electrode active material, solid electrolyte, conductive agent and Li5FeO4 are mixed in proportion and ground to obtain a composite electrode.

[0014] In the step 1, the ball milling speed is 100-800 rpm and the time is 1-20 hours.

[0015] A lithium-free negative electrode all-solid-state lithium battery comprises the positive electrode material mentioned above.

[0016] A method for reducing side reactions between the positive electrode and the solid electrolyte of a lithium-free negative electrode all-solid-state lithium battery, inhibiting the structural degradation of the electrode active material and the decomposition of the electrolyte, characterized in that the positive electrode material according to claim 1 is used on the positive electrode.

[0017] Beneficial Effects

[0018] The LFO coated on the cathode surface can act as a pre-lithiation agent to compensate for the rapid depletion of active Li in the lithium-free anode ASSB, and can also act as a protective layer between the cathode material and the electrolyte to inhibit the structural degradation of the electrode active material and the decomposition of the electrolyte, thereby reducing the side reactions between the cathode and the solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 : Positive electrode design strategy for lithium-free negative electrode ASSB. (a) Schematic diagram of lithium-free negative electrode ASSB equipped with bare NCM811 and LFO-coated NCM811 (LFO-NCM) positive electrodes during lithiation. The coated pre-lithiation agent LFO within the positive electrode material not only provides lithium supply to the entire battery, but also acts as an interfacial protection layer to inhibit the decomposition and surface degradation of the positive electrode material NCM811 and SSE LPSC. (b) XRD pattern of LFO-NCM. Inset: corresponding SEM image. (c) Corresponding EDS element distribution. Scale bar is 5μm.

[0020] Figure 2 : Characterization of interfacial reactions and structural degradation. (a) Mutual reaction energy between LPSC and lithiated / delithiated NCM811 / LFO interface. (b) Aging test of b-NCM and (c) LFO-NCM ASSBs at a constant voltage of 4.8 V after initial charge, and the corresponding EIS curves are plotted (inset). (d) Corresponding EIS fitting results of B-NCM and LFO-NCM after aging test. (e) Internal resistance of B-NCM and LFO-NCM after different cycles. (f) In situ internal cell pressure changes in the first ten cycles in B-NCM and (g) LFO-NCM ASSBs (down), and the corresponding charge and discharge curves (up). Cross-sectional SEM images of (h) B-NCM and (i) LFO-NCM after 100 cycles.

[0021] Figure 3 : Structural degradation of NCM811 / LPSC after 100 cycles. Atomic HAADF-STEM images of cycled NCM811 in (a) B-NCM and (e) LFO-NCM. Corresponding line profiles of (bd) b-NCM and (fh) LFO-NCM in three regions. S2p and P 2p XPS spectra of (i) cycled B-NCM and (j) cycled LFONCM.

[0022] Figure 4 : Electrochemical performance at room temperature. Cycling performance of lithium-free ASSB anode at 0.2C and (a) 4.3 V and (d) 4.5 V cut-off voltages. Corresponding charge / discharge curves of (b, e) LFO-NCM and (c, f) b-NCM. (g) High-load LFO-NCM cathode (NCM811: 28.82 mg cm -2 ) Cycling stability of the lithium-free anode ASSB. (h) Charge and discharge curves of the LFO-NCM all-solid-state pouch cell with lithium-free Si anode, and (i) the corresponding energy density comparison with other ASSB systems. The inset in (h) is an optical photograph of the pouch cell. The inset in (i) is a summary of the detailed battery components. DETAILED DESCRIPTION

[0023] LFO is coated on the classic LiNi 0.8 C o0.1 Mn 0.1 O2(NCM811) positive electrode material ( Figure 1a), as an interfacial protection layer in lithium-free anode ASSBs. Interface aging tests at 4.8 V, X-ray photoelectron spectroscopy (XPS), and high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) showed that the coated LFO can serve as an interfacial protection layer to mitigate interfacial side reactions between the active material and the LPSC on the cathode side, as well as the degradation of the NCM811 structure, thereby maintaining a high capacity of 84.7% after 100 cycles. More lithium provided by LFO pre-lithiation is stored in the anode, bringing greater battery stack pressure to ensure the mechanical integrity of the cathode and stable cycling. As expected, under the same test conditions, the lithium-free indium anode ASSB with LFO-coated NCM811 (LFO-NCM) cathode showed 199.7 mAh g -1 High discharge capacity.

[0024] Example 1 LFO Synthesis

[0025] LFO was prepared by mixing Li2O and Fe2O3 in a ratio of 5.5:1 using a mortar in an argon-filled glove box. The mixture was then calcined at 450°C for 15 h in a glove box to obtain LFO. Before coating on NCM811, LFO was ground by a high-energy ball mill at 400 rpm for 4 h.

[0026] Example 2 Preparation of composite electrode

[0027] The LFO-NCM composite electrode was homogenized by mixing NCM811, LFO, LPSC, and carbon fiber (VGCF) in a weight ratio of 65:3:30:2 in a mortar.

[0028] Comparative Example 1 Preparation of composite electrode without LFO layer (B-NCM)

[0029] For the B-NCM composite electrode, the ratio was the same as that of LFO-NCM except that LPSC was used instead of LFO.

[0030] After LFO is fully crushed, it is evenly coated on the surface of NCM811 through a simple ball milling process. The XRD pattern of LFO-NCM is shown in Figure 1 The scanning electron microscope (SEM) image of LFO-NCM shows that LFO can be evenly coated on the surface of NCM811. The corresponding energy dispersive spectroscopy (EDS) image shows that Fe and O elements are evenly distributed on Ni and Co elements, further confirming the uniform coating of LFO on the surface of NCM811 ( Figure 1 c). Methods of battery assembly and electrochemical measurements:

[0031] To assemble the lithium-free anode ASSB, 120 mg of LPSC was placed into a 10 mm polyaryletherketone (PEEK) cylinder and then pressed at 2 tons for 3 min. The composite cathode was then added and pressed at 2 tons for 3 min. Next, 20 μm, 100 μm, or 150 μm of indium was added to the other side of the cell and fixed on a stainless steel plate. The ASSB was charged / discharged with a constant current in the voltage range of 2.7-4.3 V or 2.7-4.5 V by the LAND battery test system with Li / Li + The aging test was constant current charging to 4.8 V and then constant voltage charging to a current of 1 μA. EIS measurements were performed on a Bio-Logic VSP-300 with a frequency range of 1 MHz to 0.1 Hz and an amplitude of 10 mV.

[0032] The NCM811 / LPSC interface was fully characterized to study the effect of the interfacial protective layer on the coated LFO. The interfacial interaction energy between LFO and NCM811 and LPSC was calculated based on first principles, as shown in Figure 2. Figure 2 The calculations show that the interface between lithiated (initial) NCM811 and LPSC is thermodynamically unstable and undergoes spontaneous decomposition reaction with a maximum decomposition energy of -0.429 eV atom -1 Once charged, the maximum reaction energy of the de-lithiated NCM811 / LPSC is -0.706 eV atom -1 , indicating an increase in the probability of spontaneous reaction. In contrast, the maximum decomposition energies of lithiated LFO / LPSC and delithiated LFO / LPCC are -0.275 eVatom, respectively. -1 and -0.317eV atom -1 , which is lower than that of NCM811 / LPSC. These indicate that LFO coated on NCM811 can enhance the interfacial compatibility with LPSC. To further study the electrochemical interfacial stability, B-NCM( Figure 2 b) and LFO-NCM (see Figure 2 c) Aging test and corresponding electrical impedance scan (EIS) after aging were performed. At a constant voltage of 4.8 V, the capacity of B-NCM is 71.8 mAh g -1 , which is significantly higher than the 34.9 mAh g of LFO-NCM. -1 The interface impedance (Rinterface) of the aged B-NCM is 27460Ω and the charge transfer impedance (Rct) is 14128Ω, while the Rinterface of the LFO-NCM is only 1387Ω and the Rct is 1217Ω ( Figure 2d). These indicate that the coated LFO layer can inhibit the interface degradation. In addition, the impedance changes of B-NCM and LFO-NCM electrodes after cycling were collected, as shown in Figure 2 e and S9. The Nyquist plot of the B-NCM electrode after 100 cycles shows that the internal resistance increases from 50 (2nd cycle) to ~380 (100th cycle) ohms, while the internal resistance of the LFO-NCM electrode increases from 82 (2nd cycle) to 150 (100th cycle) ohms. This indicates that the coated LFO layer helps to form a stable interface. The in situ internal pressure changes of ASSBs with B-NCM and LFO-NCM positive electrodes were also studied, and the pressure changes were mainly attributed to the isotropic volume expansion of the electrodes in the confined battery volume during charging. Figure 2 The f shows that the pressure change of LFO-NCM in the first cycle is 0.100MPa and remains at about 0.092MPa in the subsequent cycles. In contrast, the pressure change of B-NCM is 0.067MPa in the first cycle ( Figure 2 g), and then continued to drop to 0.035 MPa after 5 cycles. The stable high operating stack pressure in LFO-NCM can be attributed to the coated pre-lithiation agent LFO providing sufficient active lithium to the lithium-free anode ASSB, which is expected to suppress the volume change of NCM811 particles. Therefore, focused ion beam scanning electron microscopy (FIB-SEM) was further performed to obtain typical cross-sectional images after 100 cycles. B-NCM ( Figure 2 h) shows obvious particle cracks, while LFO-NCM ( Figure 2 i) The particles retain their intact morphology. These indicate that the coated pre-lithiation agent LFO can ensure the mechanical integrity of the cathode material as well as the reversible delithiation and lithiation process.

[0033] HAADF-STEM was used to study the structural degradation of NCM811 and the effect of coating LFO as an interface protection layer on NCM811 after 100 cycles. Since the image contrast of HAADF-STEM is proportional to Z1.7, where Z represents the atomic number, heavy transition metals (TM) are easily observed, while light elements such as Li and oxygen remain unobservable. Figure 3 Figure a shows the HAADF-STEM image of B-NCM from the surface to the bulk. In region 1 (bulk), the TM and Li sheets are sequentially arranged along the c-axis, showing a well-layered structure with an interlayer spacing of 0.47 nm ( Figure 3 b). A slightly disordered layer with a thickness of about 6.0 nm was observed in region 2, where TMs were detected to occupy some of the Li sites. Figure 3Figure c shows the interlayer spacing in region 2. The mixed interlayer spacing confirms the migration of TM into the Li layer. In region 3 (surface) with a thickness of about 3.1 nm, the layered structure completely disappears and transforms into a disordered rock salt phase. The nickel environment transforms into a Ni-rich phase near the surface. 2+ species (NiO), as confirmed by the interlayer spacing of 0.23 nm ( Figure 3 d), corresponding to the rock salt phase. In contrast, the LFO-protected NCM811 ( Figure 3 The structural damage of e) is effectively alleviated. From the bulk to the surface, such as Figure 3 As shown in the fh, the layered structure of LFO-NCM is well maintained, not just the surface rock salt phase structure of about 0.6 nm, which indicates that the pre-lithiation agent LFO coating can effectively serve as an interfacial protection layer on NCM811 during the repeated charge and discharge process of ASSB. In order to gain a deeper understanding of the electrochemical compatibility of LPSC with NCM811 and the coated LFO layer, XPS study of the composite cathode was performed after 100 cycles. LPSC undergoes irreversible electrochemical reactions during cycling, especially at the interface in contact with highly oxidative cathode materials at high voltage. The typical S2p and P 2p peaks of LPSC are shown. After 100 cycles ( Figure 3 i), four more pairs of S2p doublets appeared in B-NCM, which can be attributed to Li2S, P2S x 、SO3 2- and SO4 2- The P2p core-level XPS also shows a pair of x In contrast, the presence of the LFO protective layer effectively mitigates the side reactions ( Figure 3 j) The byproduct in LFO-NCM is 6.72% SO4 2- 7.16% P2S x and 18.51% Li2S, while the byproduct in B-NCM is 4.25% SO4 2- 、5.55% SO3 2- 12.75% P2S x 、28.10%Li2S.

[0034] The LFO-NCM lithium-free anode ASSB exhibited a high conductivity at 0.2C (1C = 170 mA g -1 ) is 307.4 mAh g -l , the specific discharge capacity is 187.5 mAh g –l ( Figure 4b). The charge distribution in the first cycle is inconsistent with that in the subsequent cycles, which can be attributed to the irreversible delithiation of LFO in the first cycle and the excess lithium storage on the indium anode side. This ensures that there is enough active Li in the subsequent cycles to compensate for the Li consumption of the side reactions. In contrast, the charge capacity of the lithium-free anode ASSB equipped with B-NCM in the first cycle is 221.3 mAh g -1 , the discharge capacity is 154.9mAh g-1( Figure 4 c). The discharge curves clearly show that with increasing cycle numbers, the inflection point at 3.6 V appears earlier, corresponding to the decay of the discharge capacity, which indicates that the active lithium is being rapidly depleted. The overpotential of LFO-NCM is smaller than that of B-NCM, which is consistent with previous theoretical calculations. The discharge capacity retention rate of LFO-NCM is 84.8% after 100 cycles, but the charge capacity retention rate of B-NCM is only 33.8%. With the cut-off voltage increased to 4.5 V, LFO-NCM can still maintain 165.7 mAh g after 50 cycles. - 1, while B-NCM only showed 44.5 mAh g after 5 cycles. –1 Low discharge capacity ( Figure 4 The corresponding charge / discharge curve is as follows Figure 4 As shown in e and f, the B-NCM curves do not overlap, while the LFO-NCM curves basically overlap, indicating that LFO can also improve the electrochemical performance of lithium-free anode ASSBs at high operating voltages.

Claims

1. A positive electrode material for a lithium-free negative electrode all-solid-state battery, characterized in that: include: Electrode active material, solid electrolyte, conductive agent and Li5FeO4.

2. The positive electrode material according to claim 1, characterized in that The electrode active material is selected from lithium-rich manganese-based positive electrode materials or high-nickel ternary positive electrode materials.

3. The positive electrode material according to claim 1, characterized in that The solid electrolyte is selected from a polymer solid electrolyte, an oxide solid electrolyte, and a sulfide solid electrolyte.

4. The positive electrode material according to claim 1, characterized in that The conductive agent is selected from one of carbon black, carbon fiber, carbon nanotube, conductive polymer and conductive metal.

5. The positive electrode material according to claim 1, characterized in that The weight ratio of the electrode active material, the solid electrolyte, the conductive agent and Li5FeO4 is: 50-80:1-10:20-40:0.5-5.

6. The method for preparing the positive electrode material of the lithium-free negative electrode all-solid-state battery according to claim 1, characterized in that: The steps include: Step 1, ball milling Li5FeO4; Step 2: The electrode active material, solid electrolyte, conductive agent and Li5FeO4 are mixed in proportion and ground to obtain a composite electrode.

7. The preparation method according to claim 6, characterized in that: In the step 1, the ball milling speed is 100-800 rpm and the time is 1-20 hours.

8. A lithium-free negative electrode all-solid-state lithium battery, characterized in that: The positive electrode material according to claim 1 is contained therein.

9. A method for reducing the side reaction between the positive electrode and the solid electrolyte of a lithium-free negative electrode all-solid-state lithium battery, inhibiting the structural degradation of the electrode active material and the decomposition of the electrolyte, characterized in that: The positive electrode material according to claim 1 is used as the positive electrode.

Citation Information

Patent Citations

  • Method for supplementing lithium in all-solid-state battery by using inorganic solid electrolyte

    CN116779864A

  • Negative electrode composite material, negative electrode pole piece, all-solid-state battery and preparation method

    CN118352510A

  • Dry-method lithium supplement positive electrode membrane, lithium ion battery and preparation method of dry-method lithium supplement positive electrode membrane

    CN118412554A

  • Positive electrode material and preparation method thereof, positive plate and lithium ion battery

    CN118448756A